Критерії оцінки якості процесу сепарації насіннєвої суміші - Алієв, Е. Б.; Алиев, Э. Б.; Aliiev, E. (ЦНТУ, 2018)
В результаті досліджень запропоновані узагальнюючі критерії якості виконання технологічного процесу сепарації насіннєвого матеріалу. Для технологічного процесу сепарації насіннєвої суміші, в результаті якого фракція компонента безперервно розподіляється вздовж лінії розроблено коефіцієнт розподілу. А для технологічного процесу сепарації, в результаті якого фракція компонента розподіляється дискретно, в якості узагальнюючого критерію прийнято сумарну концентрацію насіння проходу і сходу. В результате исследований предложены обобщающие критерии качества выполнения технологического процесса сепарации семенного материала. Для технологического процесса сепарации семенной смеси, в результате которой фракция компонента непрерывно распределяется вдоль линии разработан коэффициент распределения. А для технологического процесса сепарации, в результате которой фракция компонента распределяется дискретно, в качестве обобщающего критерия принято суммарную концентрацию семян прохода и схода. The breeding and seeding process requires the use of a variety of seed separators that not only purify the seed mixture from organic and inorganic impurities, but also allow the seed material to be grouped according to the physical and mechanical properties and morphological features. To assess the quality of the separation of the seed mixture on separators and seed treatment machines and technical means, it is necessary to use generalizing criteria. The analysis of literary sources showed the absence of a single generalizing and universal criterion for evaluating the quality of the separation process of seed material. Thus, the goal is to develop a generalization criterion for assessing the quality of the separation process of the seed mixture, which allows a comparative evaluation of the work of separators. Fraction of the mixture - a fraction of the seed mixture, obtained as a result of its separation by the specified physical-mechanical or morphological properties. The component fraction is a fraction containing 100% of the component that corresponds to certain physico-mechanical or morphological properties. In this case, the fraction of the mixture may include different fractions of components in different ratios. To the ideal fraction of the mixture is a single fraction of the component. As a result of the research, generalization criteria of the quality of the seed process separation process are proposed. For the technological process of seed separation separation, in which the fraction of the component is continuously distributed along the line, a distribution coefficient is developed. And for the technological process of separation, in which the fraction of the component is distributed discretely, as a generalization criterion, the total concentration of seeds of the passage and east is taken.
Критерии оценки качества процесса сепарации семенной смеси
Criteria for Assessing the Quality of the Separation Process of Seed Mixture
Keywords: сепарація; якість; критерій; насіння; суміш; процес; оцінка; сепарация; качество; критерий; семена; смесь; процесс; оценка; separation; quality; criteria; seeds; mixture; process; evaluation